1998
DOI: 10.1152/ajpheart.1998.274.1.h123
|View full text |Cite
|
Sign up to set email alerts
|

A role for the sarcoplasmic reticulum in Ca2+extrusion from rabbit inferior vena cava smooth muscle

Abstract: Ca2+extrusion from rabbit inferior vena cava smooth muscle was studied using ratiometric fura 2 fluorimetry. Concomitant blockade of the plasma membrane Ca2+-adenosinetriphosphatase (ATPase; PCMA), Na+-Ca2+exchanger, and sarcoendoplasmic reticulum Ca2+-ATPase (SERCA) completely prevented the decline in intracellular Ca2+ concentration ([Ca2+]i) normally observed when Ca2+ is removed from the extracellular space (ECS) after stimulated Ca2+ influx. Blockade of the Na+-Ca2+exchanger by removal of external Na+ red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…41), in the absence of ER Ca 2ϩ release, emptied superficial ER domains might mimic mitochondrial Ca 2ϩ buffering and facilitate the maintenance of CCE by sequestering subplasmalemmal Ca 2ϩ into the ER lumen in order to accomplish ER refilling independently from mitochondria and Ca 2ϩ concentration in the deeper cytosol. These data are in line with the initial superficial Ca 2ϩ buffer barrier concept, introduced by the VanBreemen group, in smooth muscle cells (42)(43)(44)(45) and might indicate that this landmark concept is also valid in endothelial cells.…”
Section: Discussionsupporting
confidence: 87%
“…41), in the absence of ER Ca 2ϩ release, emptied superficial ER domains might mimic mitochondrial Ca 2ϩ buffering and facilitate the maintenance of CCE by sequestering subplasmalemmal Ca 2ϩ into the ER lumen in order to accomplish ER refilling independently from mitochondria and Ca 2ϩ concentration in the deeper cytosol. These data are in line with the initial superficial Ca 2ϩ buffer barrier concept, introduced by the VanBreemen group, in smooth muscle cells (42)(43)(44)(45) and might indicate that this landmark concept is also valid in endothelial cells.…”
Section: Discussionsupporting
confidence: 87%
“…Although these two pumps essentially accomplish the same effect of rapidly reducing [Ca 2ϩ ] cyt levels, they have different physicochemical properties and regulatory mechanisms (Grover and Khan, 1992;Raeymaekers and Wuytack, 1993). Using indirect methods in a large vein, Nazer and van Breemen (1998) concluded that nearly half the cytoplasmic free Ca 2ϩ load is extruded via the PMCA, with an equal role for the SERCA and the plasma membrane Na ϩ -Ca 2ϩ exchanger in removal of the remainder. Much is known about the molecular identity of the Na ϩ -Ca 2ϩ exchanger in smooth muscle (Nakasaki et al, 1993;Juhaszova et al, 1996), although details of its isoform distribution and functionality awaits further characterization.…”
Section: B Sarcoplasmic Reticulummentioning
confidence: 99%
“…Stimulation of SERCA, PM-Ca 2ϩ -ATPase, and possibly forward NCX by elevated [Ca 2ϩ ] i while release terminates may be responsible for the downstroke of the PEinduced [Ca 2ϩ ] i oscillation (50). In this context, it would be interesting to obtain evidence for NCX reversal during each cycle.…”
Section: Mechanism Of Wavelike [Ca 2؉ ]I Oscillationsmentioning
confidence: 99%